(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the use of games in foreign language classes, its importance and advantages, useful aspects of pedagogical games in teaching and learning a foreign language. Pedagogical games used in classes are considered an active and effective method of teaching, and such activities serve to form not only the knowledge and skills of a person, but also professional and moral characteristics, i.e., such qualities as activity, creativity, creativity, community.